The multichannel challenge: channel combining for wealth - Wilson, Hugh (Henry Stewart Talks, 2008)
What senior non-marketers think of marketing, The service profit chain, Customer experience: beyond touchpoints, Changes in the use of different channels, Holistic experience of multichannels, Channel integration, Does multichannel integration matter?, Multichannel insight, Selling by bombardment, Combining channels for wealth, Integrated decision making
Archived at 2022/03/17